THE INFLUENCE OF EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE MEDIATED BY ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Awalia, Fellin Yunita; Yanuar, Yanuar (Graduate Program of Universitas Tarumanagara, 2024)
This research discusses employee engagement, organizational support, organizational citizenship behavior on employee performance at PT. XYZ. The purpose of this research is to analyze and explain the effect of employee engagement and organizational support on employee performance through organizational citizenship behavior as a mediating variable at PT XYZ. In this research using quantitative methods and questionnaires as a data collection technique. The sample for the questionnaire was 210 employees of PT XYZ. Data analysis techniques using structural equation modeling with partial least square method (PSL-SEM). The ﬁndings of this research showed that: (1) employee engagement has a positive and signiﬁcant effect on employee performance, (2) organizational support has a positive and signiﬁcant eﬀect on employee performance, (3) ocb has a positive and signiﬁcant effect on employee performance, (4) ocb mediates between employee engagement and employee performance, (5) ocb mediates between organizational support and employee performance.